Relationship between Fatigue Properties and Surface Treatment of Aluminum Alloy - Zahedi, Soroosh; Ali Khan, Umair (My University, 2023)
Corrosion has posed a significant challenge within the maritime sector for numerous years. In the 21st century, bolstering the corrosion resistance of alloys, particularly aluminum alloys, has become paramount. Aluminum alloys find widespread use in propulsion systems, boat hulls, and cargo vessels. However, their response to varying water and atmospheric conditions can differ [1]. Different techniques, such as Surface Acid Anodization (SAA) and Chromic Acid Anodization (CAA), are employed to enhance alloy corrosion resistance. Nonetheless, research indicates that anodization can lead to a reduction in fatigue strength of up to 30%. This master’s thesis seeks to examine the effectiveness of three distinct aluminum alloys, each produced through different manufacturing methods, using fatigue testing before and after anodization. The aluminum variants under scrutiny include EN AC-43100 aluminum cast in a permanent mold, AC-43400 produced via highpressure die-casting, and 6014 sheet metal. The testing employed dog bone samples with a servo fatigue test rig, utilizing the staircase fatigue method. The study also delved into crack formation and microstructural characteristics of cross-sections to investigate failure modes. The results of this investigation aim to lay the groundwork for enhancing fatigue resistance in marine applications of aluminum alloys while minimizing the potential loss of mechanical properties.
Keywords: Corrosion resistance; Fatigue; Aluminium alloys; HPDC; PMC; Sheet Metal; Anodization Molding; Casting